Associations between inactivated COVID-19 vaccination status and timing and fertility and pregnancy outcomes following frozen-thawed embryo transfer: a prospective cohort study - Liu, Danmeng; Chen, Lijuan; Cai, He; Zhou, Hanying; Wang, Min; Li, Na; Xue, Xia; Tian, Li; Mol, Ben W.; Shi, Wenhao; Shi, Juanzi (Frontiers in Endocrinology, 2025)
ObjectiveLimited evidence exists on the safety of inactivated COVID-19 vaccines and the optimal vaccination timing for women undergoing in vitro fertilization-frozen embryo transfer (IVF-FET). This study aims to examine the associations between inactivated COVID-19 vaccination status and timing and fertility and pregnancy outcomes following IVF-FET.MethodsThis was a single-center prospective cohort study conducted from 1 May to 31 December 2021, with follow-up until 15 November 2022. We studied female patients aged 20 to 47 years undergoing IVF. Participants undergoing their first FET were included in this study. Information on maternal sociodemographic and health-related factors, COVID-19 vaccination status, the IVF-ET process, and outcomes was collected. Generalized linear models or generalized estimating equation models were used to evaluate the associations between vaccination and fertility and pregnancy outcomes. We controlled for maternal characteristics and cycle characteristics, including maternal age, BMI, parity, ovarian stimulation protocol, fertilization method, endometrial preparation, and other relevant factors.ResultsA total of 2,733 eligible women were included, with 742 (27.1%) in the vaccinated group and 1,991 (72.9%) in the unvaccinated group. Among these women, 1,367 (50.0%) achieved a live birth. The incidences of clinical pregnancy and live birth were lower in the vaccinated group compared to the unvaccinated group (clinical pregnancy: 56.6% vs. 63.6%; adjusted RR: 0.92, 95% CI: 0.86, 0.98; live birth: 44.3% vs. 52.2%; adjusted RR: 0.89, 95% CI: 0.82, 0.98). These significant associations were more pronounced in women vaccinated before ovarian stimulation (clinical pregnancy: adjusted RR: 0.91, 95% CI: 0.84, 0.98; live birth: adjusted RR: 0.86, 95% CI: 0.78, 0.95), particularly in those with a ≤ 90-day interval between vaccination and ovarian stimulation. The effect size was similar but did not reach statistical significance in women vaccinated after ovarian stimulation and before FET (clinical pregnancy: adjusted RR: 0.92, 95% CI: 0.79, 1.07; live birth: adjusted RR: 0.93, 95% CI: 0.78, 1.12). No significant association was found with pregnancy outcomes.ConclusionInactivated COVID-19 vaccination may be associated with a modest reduction in IVF-FET success, particularly when administered before ovarian stimulation. However, a vaccination administered more than 90 days prior to ovarian stimulation may help mitigate these potential adverse effects.